Character Values Through The Learning Media of Kupu-Kupu Manis Dance - Lestari Raharjo, Evi Dwi; Hartono, Hartono; Syakir, Syakir (Catharsis, 2021)
The Kupu-Kupu Manis Dance (Cute Butterfly Dance) is a creative dance that comes from the Cute Butterfly song with the characteristic variety of butterfly movements when flying in the garden. This dance is used as one of the dances given in the era of the covid-19 pandemic. This study aims to provide an overview of the psychological and sociocultural character values ​​given through learning the Kupu-Kupu Manis Dance in intracurricular activities. The research was conducted using qualitative analysis research methods with the research location in RA Aisyiyah Pudakpayung Semarang. Instruments and data collection techniques used observation, interviews, and document studies. The data validity technique uses data triangulation techniques. Meanwhile, data analysis and processing techniques were carried out by collecting, reducing, clarifying, and verifying data. The character values ​​given by the teacher through the Sweet Butterfly Dance to students are expected to instill values ​​in everyday life. The value given is also an added value for students because they have been given the values ​​given earlier by the family (parents) and the surrounding environment. The value instilled in students from an early age is a good effort because it makes students know the values ​​of character education, especially through learning Kupu-Kupu Manis Dance in schools, namely RA Aisyiyah Pudakpayung Semarang.